Just and equal treatment in polygamous marriage: the practice in the Shariah Courts in Malaysia - Abdul Hak, Nora (International Islamic University Malaysia, 2008)
In Islam, a man may marry more than one woman, provided, as mentioned in the Qur’an, some conditions are observed. The requirement of equal and fair treatment to the women is clearly emphasised, and it has to be based on just and equitable principles as laid down by Islamic Law. Muslim jurists have laid down specific conditions for a man to take more than one wife. The man should have enough financial capacity to look after the needs of the women and they should be treated equally in fulfilling their rights such as maintenance and accommodation. If a man feels that he will not be able to treat the women with equality and justice he should restrict himself to marrying only one woman. In Malaysia, the Syariah Court can only grant permission for polygamous marriage if a man has satisfied the court that he has fulfilled the required conditions. Section 23 (4) of the Islamic Family Law Act in Malaysia provides that the husband must have sufficient means to support his wives and dependants, that he would be able to accord equal and fair treatment to them. There are many cases in the Syariah Court where applications to practise polygamy by men were dismissed for fear justice would not be served to the women. This paper is an observation on the practice of the Syariah Court in Malaysia in granting permission to applications for polygamous marriage, and examines briefly to what extent this requirement of equal and fair treatment is adhered to by the courts.